Polyoxometalates for bifunctional applications: catalytic dye degradation and anticancer activity - Ong, Boon Chong (2022)
Improving the efficiencies of organic compound degradations by catalytic materials is a challenging materials research field. In our research, we successfully synthesized cobalt-based polyoxometalates (CoV-POMs) via a simple crystallization-driven self-assembly method. The incorporation of the newly synthesized CoV-POMs into peroxymonosulphate (PMS), forming a mixture, greatly enhancing the catalytic activation for a complete degradation of dye solution. The positive synergic effect between CoV-POMs and PMS was substantiated by a relatively meager degradation of less than 10% in the system without CoV-POMs, in which CoV-POMs played a vital role to activate PMS towards free radicals generation for dye degradation. Methylene blue (MB) and rhodamine B (RB) dyes were completely decolorized under 60 min with the presence of 40 mg/L CoV-POMs and 150 mg/L PMS. The CoV-POMs/PMS system was pH dependance with a lower dye degradation efficiency at elevated pH. The effect of pH was more prominent in RB dye, in which the degradation efficiency dropped drastically from 93.3% to 41.12% with the increase in the solution pH from 7 to 11. The quenching tests suggested that sulfate radicals were the dominant active species involving in the dye degradation reaction. Besides MB and RB dyes, CoV-POMs/PMS system also showed significant activity towards the degradation of phenol red (PR) and methyl orange (MO) dyes. In the biological test, CoV-POMs exhibited non-toxic behavior towards normal cells that reduced safety concern for the large-scale wastewater treatment application. In addition, the testing divulged the anticancer property of CoV-POMs with more than 35 % of A549 lung adenocarcinoma and MDA-MB-231 breast adenocarcinoma were killed with 250 mg/L CoV-POMs. The selective lethality of CoV-POMs towards cancer cells was found to be caused by different extents of cellular apoptosis. In overall, the synthesized bifunctional CoV-POMs manifested superior activities in the examined applications, specifically dye degradation and anticancer.